Beneficial Effect of Etanercept on Hyperoxic Lung Injury Model in Neonatal Rats. (2nd January 2016) - Oncel, Mehmet Yekta; Yurttutan, Sadik; Alyamac Dizdar, Evrim; Gokce, Ismail Kursat; Gonul, Ipek Isik; Topal, Turgut; Canpolat, Fuat Emre; Dilmen, Ugur
ABSTRACT: Purpose: To determine whether prophylaxis with etanercept, an anti-inflammatory drug, would decrease the severity of lung injury in a neonatal rat model of bronchopulmonary dysplasia (BPD); Materials and Methods: Rat pups were divided into three groups: pups exposed to room air (group 1; n = 10), to hyperoxia + placebo (group 2; n = 9), and to hyperoxia + etanercept (group 3; n = 8). Lung morphology was assessed by alveolar surface area percentage, which is a measure of alveolar size. The severities of lung inflammation and antioxidant capacity were assessed by quantifying tumor necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β), malondialdehyde (MDA), and superoxide dismutase (SOD) from lung homogenate; Results: The percentage of alveolar surface areas were significantly higher in group 3 compared to group 2 ( p = .004) and similar in both group 1 and group 3 ( p = .21). The mean level of lung MDA was significantly higher in group 2 compared to group 1 and group 3 ( p < .05 for both). Lung homogenate SOD activities in group 3 was significantly higher than group 2 ( p < .001). Furthermore, group 3 pups had lower levels of TNF-α and TGF-β in lung homogenate than that in group 2 ( p < .05 for both) but similar in both group 1 and group 3; Conclusion: Etanercept has favorable effects on alveolarization as well as inflammation and oxidative stress markers in a neonatal rat model of BPD.